Penguatan Pertumbuhan Ekonomi Melalui Asuransi Syariah Di Indonesia - Febri Nur Rahmawati; Hindun Asmarani; Ilma Asriningtyas; Agus Eko Sujianto (Jurnal Bintang Manajemen, 2023)
The purpose of this study is to determine the strengthening of economic growth through sharia insurance. The method used in this study is to use qualitative methods by conducting library research and documentation techniques sourced from literature studies, scientific journals and written reports related to economic growth and sharia insurance. The research results show that insurance plays an important role in strengthening economic growth. Sharia insurance has an importantrole as a source of national development financing, reducing poverty, and can divert financial risks caused by unexpected events or accidents.